METHODOLOGY OF TEACHING PROGRAMMING LANGUAGES USING DIFFERENTIATED EDUCATIONAL TECHNOLOGIES IN SECONDARY SCHOOLS - Jumanquziyev Uktamjon Utkirjon ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article analyzes new methods and principles for the use of differentiated educational technologies in general secondary schools.